2000
DOI: 10.1002/jor.1100180326
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative bioassay of osteoinduction

Abstract: We developed a reproducible, relatively rapid bioassay that quantitatively correlates with the osteoinductive capacity of demineralized bone matrix obtained from human long bones. We have found that Saos human osteosarcoma cells proliferate in response to incubation with demineralized bone matrix and that an index of this proliferative activity correlates with demineralized bone matrix-induced osteogenesis in vivo. The bioassay (Saos cell proliferation) had an interassay coefficient of variation of 23 +/- 2% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Finally, it is possible that prolonged exposure of BMP-7 to HCl could have degraded a portion of it. However, 0.5 N and 0.6 N HCl have been the preferred demineralization medium for over 40 years due to the ability to remove bone mineral efficiently while leaving the graft osteoinductive (Adkisson et al 2000;Gendler 1986;Harakas 1984;Jazayeri et al 1994;Nilsson et al 1990;Pietrzak 2006;Reddi and Huggins 1972;Shigeyama et al 1995;Urist 1965;Yazdi et al 1991;Zhang et al 1997). Demineralization cycles as long as several days have been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is possible that prolonged exposure of BMP-7 to HCl could have degraded a portion of it. However, 0.5 N and 0.6 N HCl have been the preferred demineralization medium for over 40 years due to the ability to remove bone mineral efficiently while leaving the graft osteoinductive (Adkisson et al 2000;Gendler 1986;Harakas 1984;Jazayeri et al 1994;Nilsson et al 1990;Pietrzak 2006;Reddi and Huggins 1972;Shigeyama et al 1995;Urist 1965;Yazdi et al 1991;Zhang et al 1997). Demineralization cycles as long as several days have been used.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the demineralization process should maximize BMP retention by the graft. Although most protocols utilize HCl (0.5-0.6 N) for demineralization, little standardization exists (Adkisson et al 2000;Gendler 1986;Harakas 1984;Jazayeri et al 1994;Mizutani and Urist 1982;Nilsson et al 1990;Pietrzak 2006; Reddi and Huggins 1972;Shigeyama et al 1995;Swenson and Arnoczky 2003;Urist 1965;Urist et al 1968;Yazdi et al 1991;Zhang et al 1997). For instance, HCl exposures of 30 min to 30 days have been reported but there are no studies of time, as an independent variable, on retained BMP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Adkisson et al developed a "rapid quantitative bioassay of osteoinduction" by using SaOS-2 osteosarcoma cells and studied cell proliferation rates under the infl uence of DBM. However, correlation between cell proliferation and osteoinduction was not strong (Adkisson et al, 2000). Zhang et al and Wolfi nbarger and Zheng used human periosteal cells and human dermal fibroblasts to relate cellular ALP activity to DBM osteoinductivity (Wolfi nbarger and Zheng, 1993;Zhang et al, 1997).…”
Section: In Vitro Models and Choice Of Cell Typementioning
confidence: 99%
“…Interassay and intra-assay variations are a crucial concern with such heterogeneous preparations. Using 25 samples of human DBP, Adkisson et al (2000) reported that DBP stimulated DNA synthesis by human SAOS osteosarcoma cells in serum-free medium, and that the magnitude of stimulation was positively correlated (r 2 = 0.72) to the histomorphometric measure of bone area induced in athymic rats. It seems curious to identify the magnitude of stimulation of DNA synthesis as the 'osteoinductive index' when serum would have a similar effect.…”
Section: In Vitro Tests Of Osteoinductionmentioning
confidence: 99%